Calvin Coolidge - Hopper, Jennifer (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.People involved or simply interested in politics often ask whether today's political environment is more toxic than ever before. Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump presents an impartial and authoritative history of invective toward the White House so readers can determine the answer for themselves.The book focuses on the most representative and commonplace attacks of a vitriolic and personal nature, detailing who instigated and trafficked in the attacks and how presidents, administrations, and political parties defended themselves. It also illustrates how honest disagreements about policy―such as FDR's New Deal, Ronald Reagan's Central America policies, George W. Bush's invasion of Iraq, and Barack Obama's Affordable Care Act―fueled expressions of hatred and condemnation. Finally, the book includes perspectives from both the right and the left on the legitimacy of these attacks and the victims' defenses as well as their impact on American politics and policy.
Keywords: dept.psc

James Buchanan - Hopper, Jennifer (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.People involved or simply interested in politics often ask whether today's political environment is more toxic than ever before. Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump presents an impartial and authoritative history of invective toward the White House so readers can determine the answer for themselves.The book focuses on the most representative and commonplace attacks of a vitriolic and personal nature, detailing who instigated and trafficked in the attacks and how presidents, administrations, and political parties defended themselves. It also illustrates how honest disagreements about policy―such as FDR's New Deal, Ronald Reagan's Central America policies, George W. Bush's invasion of Iraq, and Barack Obama's Affordable Care Act―fueled expressions of hatred and condemnation. Finally, the book includes perspectives from both the right and the left on the legitimacy of these attacks and the victims' defenses as well as their impact on American politics and policy.
Keywords: dept.psc

Andrew Jackson - Marchant-Shapiro, Theresa (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.• Investigates a unique form of expressions of hatred toward American presidents, focusing on the personal rather than the political• Covers every president from Washington to Trump• Includes coverage of personal attacks on First Families• Details how presidents and allies responded to these attacks
Keywords: dept.psc

Reexamining the Nineteenth-Century presidency and partisan press: The Case of President Grant and the Whiskey Ring Scandal - Hopper, Jennifer Rose (Social Science History, 2018)
Studies of the institutional development of the presidency and popular leadership by presidents over time lead us to contrary expectations as to how a nineteenth-century president would react to a major political scandal. Scholarship on newspapers of the late 1800s is also unclear on how a quasipartisan media, with some outlets moving toward independence, would cover a White House scandal. I find that a close analysis of the case of President Ulysses S. Grant and the Whiskey Ring scandal forces us to reconsider what we assume to be firmly modern developments in both presidential studies and media history. Though a supposedly “premodern” president, Grant still mounted a concerted effort to mitigate the damage of the scandal. Further, although the president could get his version of events across in prominent newspapers, Republican newspaper coverage was hardly reliable. Newspapers also connected politicians’ character and psychology to mistakes made in office and made presidential strategies to shape public perception clear to their audiences—emphases on political gamesmanship considered hallmarks of the modern media environment.
1 citations (Crossref) [2023-10-31]
Keywords: dept.psc; peer-reviewed

Local Mexico: Democratic Transitions in an Authoritarian Context - Olney, Patricia (FirstForumPress, a division of Lynne Rienner Publishers, Inc., 2018)
Keywords: Local government; Mexico; dept.psc; faculty_collection

Democracy in New England: a community politics reader - Wharton, Jonathan L. (Cognella Academic Publishing, 2018)
Keywords: New England; Politics and government; dept.psc; faculty_collection